2015
DOI: 10.1002/pros.23025
|View full text |Cite
|
Sign up to set email alerts
|

Dietary, supplement, and adipose tissue tocopherol levels in relation to prostate cancer aggressiveness among African and European Americans: The North Carolina-Louisiana Prostate Cancer Project (PCaP)

Abstract: Background Controversies remain over the safety and efficacy of vitamin E (i.e., α–tocopherol) supplementation use for the prevention of prostate cancer (CaP); however, associations of different tocopherol forms and CaP aggressiveness have yet to be examined. Methods This study examined whether food intake of tocopherols, vitamin E supplement use, and adipose tissue biomarkers of tocopherol were associated with CaP aggressiveness among African-American (AA, n=1,023) and European-American (EA, n=1,079) men di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The third National Health and Nutrition Examination Survey found that serum α‐T level was inversely associated with prostate cancer risk factors: testosterone, total estradiol, and sex hormone‐binding globulin 38 . An inverse correlation between serum levels of α‐T and prostate cancer risk was found among smokers in studies by Cheng et al 39 and Weinstein et al 40 Serum levels of γ‐T (highest vs lowest quartiles) were also shown to be inversely associated with the risk of aggressive or high‐grade prostate cancer in studies by Cheng et al 39 and Bauer et al 41 In the North Carolina‐Louisiana Prostate Cancer Project, a study involving 1023 African American and 1079 European American participants, however, dietary intake of both α‐T and δ‐T were inversely correlated with prostate cancer aggressiveness, but only in European Americans 42 …”
Section: Human Studies On Ve and Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…The third National Health and Nutrition Examination Survey found that serum α‐T level was inversely associated with prostate cancer risk factors: testosterone, total estradiol, and sex hormone‐binding globulin 38 . An inverse correlation between serum levels of α‐T and prostate cancer risk was found among smokers in studies by Cheng et al 39 and Weinstein et al 40 Serum levels of γ‐T (highest vs lowest quartiles) were also shown to be inversely associated with the risk of aggressive or high‐grade prostate cancer in studies by Cheng et al 39 and Bauer et al 41 In the North Carolina‐Louisiana Prostate Cancer Project, a study involving 1023 African American and 1079 European American participants, however, dietary intake of both α‐T and δ‐T were inversely correlated with prostate cancer aggressiveness, but only in European Americans 42 …”
Section: Human Studies On Ve and Cancermentioning
confidence: 94%
“…38 An inverse correlation between serum levels of α-T and prostate cancer risk was found among smokers in studies by Cheng et al 39 and Weinstein et al 40 Serum levels of γ-T (highest vs lowest quartiles) were also shown to be inversely associated with the risk of aggressive or high-grade prostate cancer in studies by Cheng et al 39 and Bauer et al 41 In the North Carolina-Louisiana Prostate Cancer Project, a study involving 1023 African American and 1079 European American participants, however, dietary intake of both α-T and δ-T were inversely correlated with prostate cancer aggressiveness, but only in European Americans. 42 The importance of nutritional levels of VE in influencing prostate cancer is also supported by a nested case-control study in the US, showing that three single-nucleotide polymorphism (SNP) variations (involving BUD13, ZNF259, and APOA5), which resulted in higher circulating α-T levels, were correlated with a lowered risk of prostate cancer. 43 More recently, three additional SNP variations (involving SEC14L2, we SOD1, and TTPA) were found to be associated with a lower risk of prostate cancer in subjects receiving VE in the SELECT.…”
Section: Prostate Cancermentioning
confidence: 94%
“…In an observational trial, Antwi et al investigated whether the use of vitamin E supplements was associated with prostate cancer risk in the North Carolina–Louisiana Prostate Cancer Project 115 . Study results showed no association with reported use of vitamin E supplements in the 12 months prior to study enrollment, with varying doses consumed.…”
Section: Vitamin Ementioning
confidence: 99%
“…These findings suggest that greater intake of food containing these micronutrients might be beneficial to men with PSA‐defined recurrent prostate cancer. The North Carolina‐Louisiana Prostate Cancer Project examined whether dietary intake of tocopherols, vitamin E supplement use, and adipose tissue biomarkers of tocopherols were associated with prostate cancer aggressiveness among African‐American and European‐American men . Dietary intake of α‐T and δ‐T were inversely related to prostate cancer aggressiveness in European‐Americans .…”
Section: Studies On Tocopherols and Human Cancersmentioning
confidence: 99%